A SWITCHING ALGORITHM USING MODIFIED SELECTION SORT FOR THE REDUCTION OF IMPULSE NOISE - K. Vasanth; S. Karthik (ICTACT Journal on Image and Video Processing, 2010)
A novel algorithm is proposed for the restoration of images corrupted by impulse noise; this work aims at a novel filter whose window size is fixed (3X3) for all noise densities. The new algorithm significantly produces better image quality than standard median filter (SMF), adaptive median filters (AMF), and center weighted median filter (CWMF) and threshold decomposition filter (TDF). Unlike the other filters, the proposed algorithm computes median if and only if there is a corrupted pixel and replaces it by the median value, if the median is corrupted then average of uncorrupted pixels in the current processing window is replaced else preprocessed pixel value is replaced. The proposed method removes the noise effectively even at noise level as high as 85% and preserves the edges without any loss up to 80% of noise level. The proposed algorithm (PA) is tested on different images and is found to produce better results in terms of the qualitative and quantitative measures.